[PP.29.25] ASSOCIATION OF PHERIPHERAL AND CENTRAL BLOOD PRESSURE WITH THE COMPONENTS OF METABOLIC SYNDROME IN A MEXICAN SAMPLE. (September 2016) - Quezada, P.; Grover, F.; Ramos, C.; Pascoe, S.; Cardona, E.; Hernandez, S.
Abstract : Objective: The aim of this study is to associate peripheral and central blood pressure with the components if metabolic syndrome in a mexican sample. Design and method: 82 Mexican subjects were evaluated in this cross-sectional study to investigate the distribution of central systolic blood pressure values estimated by the Omron HEM-9000AI device, with at least 1 of the 5 cluster components in accordance with NCEP ATPIII criteria as the simultaneous alteration in equal or more than 3 of the 5 components: abdominal obesity (W), high triglycerides (T), low HDL cholesterol (H), elevated blood pressure (B), and elevated fasting glucose (G). Results: We catalogue the sample in four groups and were used for the present analysis. Estimated central systolic blood pressure was higher than braquial systolic blood pressure and was significantly correlated with the presence of B in the groups (p = 0.000). The central blood pressure values obtained from subject with MetS in presence of B were 144.9 ± 18.2 (n = 24) mmHg. The values obtained from subject with MetS whitout including blood pressure were 122.8 ± 12.4 (n = 16) mmHg; from subjects with less than 3 cluster but with the presence of B were 142.9 ± 16.7 (n = 18) mmHg and 124.7 ± 9.9 mmHg for normal blood pressure categories with less than 3 components cluster criteria (n = 23). Conclusions: In conclusion, beside different component clusters of MetS showed varying associations with central blood pressure, the single presence of elevated blood pressure, is sufficient to increase that value than having more cluster components of MetS as a whole.